2001
DOI: 10.2527/2001.793642x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of farmers' behavior on calves' reactions to transport and quality of veal meat.

Abstract: The relationships between farmers' behavior toward veal calves, calves' responses to handling and transport, and veal meat quality were assessed. Two groups of 10 veal units were selected based on previous observed farmers' behavior toward the calves: one group consisted of farmers who had shown predominantly "positive" behavior toward the calves, and the other group of farmers had shown predominantly "negative" behavior. Calves were observed for their reactions to people at the unit, and 20 calves per veal un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 28 publications
3
64
0
7
Order By: Relevance
“…Sartorelli et al (1992) showed that cortisol levels increase during the first 30 to 60 min of transport and then remain stable. Heart rate is initially high, but decreases gradually over a period by 30 to 60 min of transport, reaching values of 10% to 25% above the basic level (Lensink et al, 2001;Van de Water et al, 2003;Grigor et al, 2004). These physiological changes are most probably related to emotional stress due to the unfamiliar situation and to physical effort related to loading and to keep balance in the moving and vibrating lorry (cf.…”
Section: Veal Calves and Adult Cattlementioning
confidence: 99%
See 4 more Smart Citations
“…Sartorelli et al (1992) showed that cortisol levels increase during the first 30 to 60 min of transport and then remain stable. Heart rate is initially high, but decreases gradually over a period by 30 to 60 min of transport, reaching values of 10% to 25% above the basic level (Lensink et al, 2001;Van de Water et al, 2003;Grigor et al, 2004). These physiological changes are most probably related to emotional stress due to the unfamiliar situation and to physical effort related to loading and to keep balance in the moving and vibrating lorry (cf.…”
Section: Veal Calves and Adult Cattlementioning
confidence: 99%
“…The animals have to leave their familiar pen or environment and sometimes social group, are handled and are introduced into the unfamiliar environment of the lorry, sometimes containing unfamiliar animals. The whole loading procedure causes an increase in the blood cortisol rate and an increase in the heart rate of approximately 80% in calves, compared to home pen levels (Lensink et al, 2001; Van de Water et al, 2003). Loading conditions, especially equipment (loading ramp and quay), determine largely levels of psychological stress and physical effort.…”
Section: Veal Calves and Adult Cattlementioning
confidence: 99%
See 3 more Smart Citations